2011
DOI: 10.1016/j.ahj.2010.11.020
|View full text |Cite
|
Sign up to set email alerts
|

The Occluded Artery Trial (OAT) Viability Ancillary Study (OAT-NUC): Influence of infarct zone viability on left ventricular remodeling after percutaneous coronary intervention versus optimal medical therapy alone

Abstract: Background The Occluded Artery Trial (OAT) showed no difference in outcomes between percutaneous coronary intervention (PCI) vs. optimal medical therapy (MED) in patients with persistent total occlusion of the infarct related artery (IRA) 3–28 days post-MI. Whether PCI may benefit a subset of patients with preservation of infarct zone (IZ) viability is unknown. Methods and Results The OAT nuclear ancillary study hypothesized that; 1) IZ viability influences left ventricular (LV) remodeling, and that 2) PCI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 25 publications
1
32
0
1
Order By: Relevance
“…showed that 31% of patients did not have a preserved viability (severely reduced viability group) defined as at least 40% of the marker uptake [23].…”
Section: Pci + Omt (N = 21)mentioning
confidence: 99%
“…showed that 31% of patients did not have a preserved viability (severely reduced viability group) defined as at least 40% of the marker uptake [23].…”
Section: Pci + Omt (N = 21)mentioning
confidence: 99%
“…Напротив, у пациентов с преимущественно рубцовыми изменениями на блюдается неблагоприятное ремоделирование ЛЖ, проявляющееся в увеличении конечносистоличе ского и конечнодиастолического объемов. Udelson et al [43] в исследовании Occluded Artery Trial (OAT) проанализировали подгруппу, включавшую 124 пациента с окклюзиями коронарных артерий, прошедших ОФЭКТ с технецием и нитроглицери новой пробой перед рандомизацией и через один год наблюдения. Через год не было выявлено до стоверных различий в изменении конечнодиасто лического или конечносистолического объема у пациентов со значительно или умеренно сниженной жизнеспособностью миокарда, а также различий при сравнении результатов в зависимости от вида проведенного лечения (ангиопластика или только медикаментозная терапия).…”
Section: жизнеспособность и прогнозunclassified
“…In this study, 1212 patients with an ejection fraction of less than 35% and coronary artery disease were randomized to undergo CABG alongside optimal medical therapy (OMT) or OMT alone [16]. The 5 year follow up of this study, published in 2011, involving patients with ICM, did not demonstrate an overall mortality benefit with revascularization in comparison to medical treatment alone for ischemic patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 1212 patients with an ejection fraction of less than 35% and coronary artery disease were randomized to undergo CABG alongside optimal medical therapy (OMT) or OMT alone [16]. The 5 year follow up of this study, published in 2011, involving patients with ICM, did not demonstrate an overall mortality benefit with revascularization in comparison to medical treatment alone for ischemic patients [16]. However, surprisingly, the ten year follow up of this largest completed trial to date, involving patients with ICM, published in 2016, showed a mortality rate of 58.9% (359 patients) in the CABG group and of 66.1% (398 patients) in the medical-therapy group (hazard ratio with CABG vs. medical therapy, 0.84; P=0.02 by log-rank test) [17].…”
Section: Introductionmentioning
confidence: 99%